The status of freshwater and reused treated wastewater for agricultural irrigation in the Occupied Palestinian Territories - Hilmi S. Salem (IWA Publishing, 2021)
Global freshwater scarcity is imposing the demand for using non-conventional water resources for irrigation and non-irrigation purposes. Direct reuse of treated wastewater for agricultural irrigation is a widespread practice in arid and semi-arid regions, because of water shortage and scarcity. Water scarcity and the need for ecological sustainability have led to the introduction of treated wastewater as an additional water resource in the national water resources' management plans of Mediterranean countries. The use of wastewater for irrigation is an important tool for water resources' supplement. However, the reuse of effluent in irrigation can have negative impacts on crop quality and soil conditions, as well as on public health and the environment. Furthermore, inappropriate management of agricultural irrigation with treated wastewater can also pose problems for plant production and the physical and chemical properties of soils. This paper presents some approaches to understand the impacts of reusing treated wastewater. It also presents a critical analysis of the treated wastewater's reuse for irrigation in the Occupied Palestinian Territories (OPT), while shedding light on the water status in the OPT. The paper investigates the wastewater treatment and reuse for agricultural irrigation, especially in the lack of control of Palestinians on their own freshwater resources in the OPT.